2003
DOI: 10.1117/12.488186
|View full text |Cite
|
Sign up to set email alerts
|

MWIR and LWIR spectral signatures of water and associated materials

Abstract: Spectral infrared emissivity measurements have been made of a variety of materials both with and without surface water. The surface water was either natural, in the form of dew or residual rainwater, or artificially introduced by manual wetting. Materials naturally high in water content were also measured. Despite the rather diverse spectral population of the underlying materials, they exhibited very similar, featureless, water-like spectra; spectrally flat with a very high magnitude across the emissive infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Additionally, moistening of the skin surface due to perspiration may lead to difficulties in evaluating the temperature of the skin. Although sweat emissivity has not been determined, a coating of dew presented emissivity values as high as human skin (35), and hence, a low potential to modify skin surface emissivity could be expected. Nevertheless, Ammer suggested that a water coating on the skin due to "profuse" sweating might act as a filter for the emitted infrared radiation from the skin surface (36) , even if the water layer is just a few microns as determined for other types of surfaces (35).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, moistening of the skin surface due to perspiration may lead to difficulties in evaluating the temperature of the skin. Although sweat emissivity has not been determined, a coating of dew presented emissivity values as high as human skin (35), and hence, a low potential to modify skin surface emissivity could be expected. Nevertheless, Ammer suggested that a water coating on the skin due to "profuse" sweating might act as a filter for the emitted infrared radiation from the skin surface (36) , even if the water layer is just a few microns as determined for other types of surfaces (35).…”
Section: Introductionmentioning
confidence: 96%
“…Significant perspiration induced by strenuous exercise is expected to dramatically alter the thermal facial signature, because water is a strong absorber of thermal radiation and dominates IR measurements. Mitchell et al showed that a layer of water only 10 microns in depth will be optically thick in the IR spectrum [35]. Furthermore, the non-uniform distribution of pores in the face is expected to lead to significant nonlinear distortions of the thermal facial signature with strenuous exercise.…”
Section: Effect Of Experimental Conditionsmentioning
confidence: 99%
“…Such pristine databases are appropriate for material identification or spectral unmixing applications, but they fail to capture the variability in reflectance that can arise in outdoor natural settings, and is necessary for realism in synthetic image generation applications. There has been some work in characterizing the effects of disturbances on soils 17 and measurements of the effects of thin layers of water, 18 but no previous work could be found that conducted a systematic study of the impact on spectra of environmental contaminants for several man-made surfaces.…”
Section: Spectral Databases and Related Workmentioning
confidence: 99%